Proceedings of the 38th International Conference on Software Engineering 2016
DOI: 10.1145/2884781.2884847
|View full text |Cite
|
Sign up to set email alerts
|

The impact of test case summaries on bug fixing performance

Abstract: Automated test generation tools have been widely investigated with the goal of reducing the cost of testing activities. However, generated tests have been shown not to help developers in detecting and finding more bugs even though they reach higher structural coverage compared to manual testing. The main reason is that generated tests are difficult to understand and maintain. Our paper proposes an approach, coined TestScribe, which automatically generates test case summaries of the portion of code exercised by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Search-based unit test generation has been extensively investigated by prior studies [13,15,29]. These studies have confirmed that it achieves a high level of coverage [15,29], detects faults in real-world applications [2,16], and reduces the debugging costs [30]. Most search-based unit test generation approaches abstract the source code of a method to a control flow graph: Definition 1 (Control Flow Graph (CFG) [1]).…”
Section: Search-based Unit Test Generationmentioning
confidence: 99%
“…Search-based unit test generation has been extensively investigated by prior studies [13,15,29]. These studies have confirmed that it achieves a high level of coverage [15,29], detects faults in real-world applications [2,16], and reduces the debugging costs [30]. Most search-based unit test generation approaches abstract the source code of a method to a control flow graph: Definition 1 (Control Flow Graph (CFG) [1]).…”
Section: Search-based Unit Test Generationmentioning
confidence: 99%
“…Moreno et al have developed Java class-level summarization approaches [8] while others focus on the method level such as Sridhara et al [11], McBurney et al [7], Rastkar et al [10] and Haiduc et al [3]. There is less work translating Java test code all approaches (Zhang et al [12], Kamimura and Murphy [4], Li et al [5] and Panichella et al [9] adapt the template-based source code approaches, and also use similar approaches for distinguishing parameters. However, in no case is such fine-grained attention paid to the conversion of the assert statements, especially the special cases for assertThat.…”
Section: Related Workmentioning
confidence: 99%
“…Many existing works have shown the feasibility and benefits of this approach by summarizing Java methods and classes [3,7,8,10,11]. Recently, these works have been adapted for the summarization of unit test code, and summaries of JUnit test cases have been shown to improve the understandability of test cases [4,5,9,12]. While these test summarization approaches result in readable summaries, they provide heuristics for converting only a limited subset of the complex-but-critical assert statement API.…”
Section: Introductionmentioning
confidence: 99%
“…But their paper expose the main ones. Panichella et al [2016] explained it is difficult to understand the result of generated test. In fact, generated tests are hard to maintain and provide unusable data for "simple" developers.…”
Section: Related Workmentioning
confidence: 99%